GeoGebra Enhances Mathematical Conceptual Understanding in Straight-Line Equations - Afriansyah, Ekasatya Aldila; Aini, Gita Fitri (Plusminus: Jurnal Pendidikan Matematika, 2025)
Rendahnya pemahaman konsep matematis menyebabkan siswa kesulitan memahami materi abstrak seperti persamaan garis lurus. Penelitian ini bertujuan menguji efektivitas GeoGebra sebagai media pembelajaran untuk meningkatkan pemahaman konsep tersebut. Metode yang digunakan adalah eksperimen (one-shot case study) dengan sampel 30 siswa kelas VIII di SMP Kec. Bayongbong (purposive sampling). Data dikumpulkan melalui tes uraian dan observasi aktivitas siswa, kemudian dianalisis secara statistik deskriptif dan inferensial (uji-z). Hasil menunjukkan bahwa GeoGebra tidak efektif dalam meningkatkan pemahaman konsep matematis. Temuan ini menyiratkan perlunya integrasi GeoGebra dengan metode lain, seperti scaffolding guru atau pembelajaran berbasis masalah. The limited comprehension of mathematical concepts by students hinders their ability to grasp abstract material, such as linear equations. The objective of this study is to assess the efficacy of GeoGebra as a learning medium to enhance comprehension of the concept. The method employed was an experiment (one-shot case study) with a sample of 30 students in class VIII at SMP Kec. Bayongbong (purposive sampling). The data were collected through the implementation of descriptive tests and student activity observations. Subsequent to the collection of the aforementioned data, the data were analyzed descriptively and inferentially (z-test). The findings indicated that GeoGebra did not demonstrate efficacy in enhancing mathematical concept comprehension. This finding suggests the necessity for GeoGebra integration with alternative methods, such as teacher scaffolding or problem-based learning.